2006
DOI: 10.3892/ijmm.18.5.893
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of non-anaphylactogenic anti-IgE antibody on the development of dextran sulfate sodium-induced colitis

Abstract: Abstract. Inflammatory bowel disease (IBD) is a spectrum of immune-mediated chronic disorders of the intestine. Patients with IBD tend to exhibit significantly elevated levels of IgE in their serum. In general, the pathogenesis of IBD exhibits inflammatory events such as immunoglobulin E (IgE)-mediated hypersensitivity. We examined the effect of the non-anaphylactogenic anti-IgE antibody, which has been known to block IgE functions, in an animal model of ulcerative colitis induced by the oral intake of dextran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…With respect to the biological ramifications of this finding, the presence of an oversulfated chondroitin sulphate within a heparin preparation could provoke increased side effects as highly sulfated polysaccharides, such as dextran sulfate, have been shown to be potent mediators of the immune response, including hypersensitivity (16,17). The structural determination of this contaminant provides a way to identify a plausible biological role, either direct or indirect, in the onset of such adverse clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the biological ramifications of this finding, the presence of an oversulfated chondroitin sulphate within a heparin preparation could provoke increased side effects as highly sulfated polysaccharides, such as dextran sulfate, have been shown to be potent mediators of the immune response, including hypersensitivity (16,17). The structural determination of this contaminant provides a way to identify a plausible biological role, either direct or indirect, in the onset of such adverse clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…A critical role for IgE has also been uncovered in a dextran sulfate sodiuminduced mouse model of colitis, where blocking IgE reduced most of the clinical signs of disease. 43 Mechanistically, IgE binds to the FcR␣1 on the surface of mast cells, and second exposure to antigen results in cross-linking of bound IgE and mast cell degranulation with release of potent inflammatory mediators. 44,45 Previous studies have shown that the anti-IgE monoclonal antibody, which binds IgE at the FcR␣1 binding site, prevents IgE from binding to the receptor on mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…29 IgE has been implicated in the pathogenesis of IBD, as well as providing protective immunity against some gastrointestinal nematodes. 13,30 Kang et al 31 reported that anti-IgE antibodies may be useful therapeutic agents for ulcerative colitis, because they inhibit the activation of Fc RIIb. IgM has anti-inflammatory properties, and IgM auto-antibodies have been reported to protect mice against influenza virus infection.…”
Section: Resultsmentioning
confidence: 99%